2019
DOI: 10.3390/ijfs7020032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Speculators’ Position Changes on the LME Futures Market

Abstract: This paper employs Granger causality tests to analyze the role of speculators using weekly COTR (commitment of traders reports) data covering the period of August 2014 to July 2017. The paper presents statistically significant evidence that the position changes of speculators, such as hedge funds and CTAs (commodity trading advisors), unidirectionally Granger-cause the prices of base metals, such as aluminum, copper, and zinc. This finding is a result of causality going from the levels of net futures positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Oversupplied concentrates in the copper mine increase smelting capacity utilization, which increases TC and refines copper quantity quickly. This stylized fact intensifies speculative investment flows, such as hedge funds and commodity funds, so that LME copper price is affected by this market expectation (Park 2019b). The rigorous negative relationship may give commodity traders arbitrage possibilities.…”
Section: Empirical Regression Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oversupplied concentrates in the copper mine increase smelting capacity utilization, which increases TC and refines copper quantity quickly. This stylized fact intensifies speculative investment flows, such as hedge funds and commodity funds, so that LME copper price is affected by this market expectation (Park 2019b). The rigorous negative relationship may give commodity traders arbitrage possibilities.…”
Section: Empirical Regression Resultsmentioning
confidence: 99%
“…First, Canarella and Pollard (1986) and MacDonald and Taylor (1988) found that the LME was efficient, while Otto (2011) and Park and Lim (2018) found opposing results. Second, Park (2019b) presented statistically significant evidence that the speculators Granger-caused the prices of base metals. Third, Figuerrola-Ferretti and Gilbert (2008) examined copper volatilities, while Park (2018) provided the evidence of volatility transmission between oil and LME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that some indications of financialization in the copper price explained the price dynamics using the VAR model. Park (2019) employed Granger causality tests to analyze the role of speculators using weekly COTR (Commitment of Traders Reports) data, and presented statistically significant evidence that the position changes of speculators, such as hedge funds, Granger-cause the prices of base metals, such as aluminum, copper and zinc among the six base metals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent years have seen a rapid growth in the participation of investors in the commodity market, in what is being called the 'financialization' of commodity markets (Cheng and Xiong 2014). This phenomenon has occurred where the commodity markets have become important, as institutional investors have come to regard commodities as an alternative asset class (Park 2019). Tang and Xiong (2012) concluded that the financialization of commodity markets through institutional investors' index funds has significantly impacted market dynamics and volatilities in commodity markets.…”
Section: Introductionmentioning
confidence: 99%